Cross-talk between LRRK2 and PKA: implication for Parkinson's disease?. (8th February 2017) - Greggio, Elisa; Bubacco, Luigi; Russo, Isabella
Abstract : Evidence indicates that leucine-rich repeat kinase 2 (LRRK2) controls multiple processes in neurons and glia cells. Deregulated LRRK2 activity due to gene mutation represents the most common cause of autosomal dominant Parkinson's disease (PD). Protein kinase A (PKA)-mediated signaling is a key regulator of brain function. PKA-dependent pathways play an important role in brain homeostasis, neuronal development, synaptic plasticity, control of microglia activation and inflammation. On the other hand, a decline of PKA signaling was shown to contribute to the progression of several neurodegenerative diseases, including PD. In this review, we will discuss the accumulating evidence linking PKA and LRRK2 in neuron and microglia functions, and offer an overview of the enigmatic cross-talk between these two kinases with molecular and cellular implications.